Knowledge management and information systems : strategies for growing organizations - Mellor, Robert B. (Houndmills, UK. : Palgrave MacMillan, 2011)
'Knowledge Management and Information Systems Strategy for Growing Organizations examines the role that information systems play in helping SMEs use knowledge to achieve strategic organizational goals. Adopting a business perspective, it is ideal for students studying strategic information systems and knowledge management'--
Includes index.
Keywords: Knowledge management; Information resources management